Synthesis, Characterisation and biological activity for binuclear complexes with Co(II), Cu(II) and Zn(II) with new ligand m-phenylendi(azo-2-naphthol) ligand type N2O2. - Al-Saedi, W. A. J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this work, the(m-phenylenediamine) and (2-naphthol) have been used in the synthesis of tetradentate ligand [m-phenylenedi(azo-2-naphthol)][H2L] type (N2O2). The ligand was refluxed in the ethanol with the metal ions [Co(II), Cu(II) and Zn(II)] salts, using triethyleamine as a base in (2:2) molar ratio to give the binuclear complexes. These complexes were characterised by (A.A), F.T.I.R, (U.V-Vis) spectroscopies, along with conductivity, chloride content and melting point measurement. These studies revealed an octahedral geometries for Co(II), Cu(II) and Zn(II) complexes with the general structure [M2(L)2(H2O)4]. The ligand and its complexes exhibited biological activity against the Bacillus(G+) strain and the Pseudomonase(G-)strains. Keyword: m-phenylene, azo, 2-naphthol